A checklist and provisional atlas of the Cicadoidea fauna of Slovenia (Homoptera: Auchenorrhyncha) - Gogala, Matija (Acta entomologica slovenica (Ljubljana), 1999)
9 species of singing cicadas are listed for the territory of Slovenia, two of them for the first time: Cicadatra atra Olivier and Tettigetta dimissa (Hagen). Published records are cited; new records are based on collected specimens and recorded or heard songs. Distributional maps of all species are added.
Keywords: favna; Hemiptera; Homoptera; Slovenia; Slovenija; škržati; zoogeografija; zoologija; zoology